Disposable E-Cigarette Use Prevalence, Correlates, and Associations With Previous Tobacco Product Use in Young Adults. Issue 3 (11th August 2021) - Leventhal, Adam M; Dai, Hongying; Barrington-Trimis, Jessica L; Tackett, Alayna P; Pedersen, Eric R; Tran, Denise D
Abstract: Introduction: Novel, inexpensive disposable e-cigarettes widely sold in attractive flavors might be exempt from US federal regulations. To inform regulatory and public health priorities, this study examined young adult disposable e-cigarette use uptake among existing tobacco users versus non-users and possible use correlates that could be potential regulatory targets. Aims and Methods: Prospective cohort data were analyzed in 2021. Among baseline (2018–2019) never disposable e-cigarette users ( n = 1903; mean [SD]: 19.3 [0.8] years-old), we tested prospective associations of baseline tobacco product use with follow-up (2020) disposable e-cigarette use initiation, followed by stratified analyses distinguishing baseline exclusive and dual e-cigarette/combustible tobacco use. Exploratory cross-sectional associations of tobacco-related correlate with vaping frequency among current disposable users ( n = 266) were tested. Results: Follow-up ever disposable e-cigarette use initiation was higher among baseline former (22.1%) and current (50.2%) versus never (6.3%) rechargeable (non-disposable) e-cigarette users. In stratified analyses, follow-up disposable e-cigarette use initiation was 0% in baseline never-vaping exclusive current smokers, higher in baseline never-vaping former smokers versus never users of any tobacco product (18.2% vs. 5.7%; adjusted odds ratio [95% CI] = 3.9 [2.1–7.5]), and higher among baseline current dual users versus never-smoking exclusive current vapers (61.3% vs. 42.2%; adjusted odds ratio [95% CI] = 3.0 [1.5–6.0]). Among follow-up current disposable e-cigarette users (overall prevalence = 10.9%), using ice-flavored (vs. fruit/sweet-flavored) e-cigarettes (adjusted rate ratio [95% CI] = 1.5 [1.0–2.1]) and vaping dependence symptoms (adjusted rate ratio [95% CI] = 2.2 [1.5–3.2]) were cross-sectionally associated with more past-month disposable e-cigarette use days. Conclusions: Young adult disposable e-cigarette use was of appreciable prevalence, including among tobacco product never users and former smokers. Regulation of disposable e-cigarettes, including ice-flavored products, might benefit young adult health. Implications: Sales of disposable e-cigarette products increased significantly in the United States from 2019 to 2020. These products contain high nicotine concentrations and various flavors that may appeal to young people. This study provides the first evidence that disposable e-cigarette use may be common among young adults, including among tobacco product never users and former smokers. Frequency of disposable e-cigarette use was positively associated with using ice-flavored e-cigarettes and vaping dependence. Regulatory policies and enforcement strategies addressing disposable e-cigarettes merit consideration in young adult health policy and prevention priorities.